The Role of the External Assessment of Educational Achievements in Improving the Efficiency of Educational Process (Journal of Educational Sciences, 2017)
This article presents the results of an external assessment of educational achievements in 2014-2016. The results of the EAEA have been comparatively analyzed in the context of higher education institutions’ status, majors and students’ contingent. The cluster analysis by the traditional system of evaluation has been conducted on the results of the EAEA of 2014-2016 years in the context of the status of universities (national, state, joint-stock and private). Results of the EAEA -2016 are given as diagrams that demonstrate the comparative data of test results of students studying by state scholarship and who pay tuition fees. 2014-2016 year the EAEA results are presented in the form of traditional and credit evaluation system. The comparative analysis has been conducted on the major «Social sciences, economics and business» in the context of university status and of national universities; results of 2015-2016 are given. It is presented a data with the number of students who received «excellent», «good», «satisfactory» and «unsatisfactory» on the EAEA. The EAEA A results are indicated according to the majors of universities: multi-disciplinary, humanitarian-economic, pedagogical, technical. The article shows annual dynamics of the EAEA results. The website of the National Testing Centre www.testcenter.kz.Key words: monitoring of education, external evaluation of educational achievement, cluster analysis.